Learning the Qur'an in Improvement Faith and piety in the Kindergarten of Harapan Ibu Sungai Baung Sarolangun Regency Jambi Province - Nurhidayati Nurhidayati (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to describe how the ability to read short verses of Surah Al-Ikhlas for early childhood 5-6 years in Harapan Ibu Sungai Baung Kindergarten, Sarolangun Regency, Jambi Province, how to implement a religious center learning in Harapan Kindergarten , Ibu Sungai Baung, Sarolangun Regency and how implementation of religious center learning in improving the ability to read short verses of Surah Al-Ikhlas for early childhood in the Harapan Kindergarten of Ibu Sungai Baung, Sarolangun Regency, Jambi Province. This study uses a qualitative approach, which is a method used to find the broadest knowledge of the object of research at the time the research is carried out. The approach used in this research is descriptive research approach. The findings and analysis of the research are, 1) The ability to read short paragraphs of letters for early childhood in the Harapan Kindergarten of Ibu Sungai Baung, Sarolangun Regency 2) Learning Center for Early Childhood Religion at the Harapan Kindergarten of Ibu Sungai Baung, Sarolangun Regency. 3) Learning Center for Early Childhood Religion at Kindergerten of Harapan Ibu Sungai Baung, Sarolangun Regency In general, learning at religious centers improves the ability to read short verses of Surah al-Ikhlash in early childhood 5-6 years